2019
DOI: 10.1021/jacs.8b13898
|View full text |Cite
|
Sign up to set email alerts
|

“Dual-Key-and-Lock” Ruthenium Complex Probe for Lysosomal Formaldehyde in Cancer Cells and Tumors

Abstract: Biomedical investigations reveal that excessive formaldehyde generation is possibly a critical factor for tissue cancerization, cancer progression and metastasis. Responsive molecular probes that can detect lysosomal formaldehyde in live cells and tumors and monitor drug-triggered formaldehyde scavenging contribute potentially to future cancer diagnosis and treatment monitoring. Herein, a novel "dual-key-and-lock" strategy-based ruthenium(II) complex probe, Ru-FA, is reported as an effective tool for formaldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 61 publications
(125 reference statements)
0
81
0
Order By: Relevance
“…The major part is the six coordinated Ir(III) part, which is both a good chemotherapeutic drug and radiotherapy drug, and at the same time, it has strong luminescence emission. In order to accurately visualize the location of tumor sites, the prodrug Ir-NB is designed to include another two parts: one is a nitrobenzoyl motif, a strong electron acceptor, which can be used to quench the luminescence emission of the Ir(III) complex owing to the photoinduced electron transfer (PET) process; 18,27 the other one is an acidity-sensitive imine bond, which can be used as a pH responsive linker to be broken in the TME to reproduce the luminescence emission of the Ir(III) complex (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…The major part is the six coordinated Ir(III) part, which is both a good chemotherapeutic drug and radiotherapy drug, and at the same time, it has strong luminescence emission. In order to accurately visualize the location of tumor sites, the prodrug Ir-NB is designed to include another two parts: one is a nitrobenzoyl motif, a strong electron acceptor, which can be used to quench the luminescence emission of the Ir(III) complex owing to the photoinduced electron transfer (PET) process; 18,27 the other one is an acidity-sensitive imine bond, which can be used as a pH responsive linker to be broken in the TME to reproduce the luminescence emission of the Ir(III) complex (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…However, research has revealed that the nasal route or inhalation is the most common and prominent route of FA exposure, because most indoor contaminants have been found in gaseous form in the air [99]. The continuous and delayed exposure with FA is associated with a broad range of serious health concerns such as various types of cancers including cutaneous carcinoma and sinus carcinoma, causes allergy, and also produces a mutagenic effect [100]. Moreover, long-term exposure with a high intensity of FA led to increasing the risk of myeloid leukemia progression [101].…”
Section: Formaldehyde Transmission Routes and Health-related Effectsmentioning
confidence: 99%
“…1B). 38 The reaction between formaldehyde and Ru-FA occurs at pH < 6.0, resulting in cleavage of 2,4-dinitrobenzene (DNB) electron acceptor to form Ru-NR and thus turn "ON" luminescence (DoL: 19.8 nM). Different with the morpholine-guided lysosome targeting, this "dual-key-and-lock" probe precludes false positive signals derived from the probe being triggered "ON" in other organelles and then accumulated in lysosome.…”
Section: "Dual-key-and-one-lock" Probementioning
confidence: 99%